Consequences of internalization and phagocytosis of Listeria during an infectious process - Yu. N. Odintsov; V. M. Perelmuter (Бюллетень сибирской медицины, 2003)
In the article there have been discussed the consequences of Listeria internalization and phagocytosis depending on hepatocyte and macrophage receptors type (Met, gC1q-R, C3b-R, Fc-R). It has been supposed that internalization and phagocytosis variant depended on the stage (inductive stage, IgM synthesis stage, IgG synthesis stage) of immunogenesis developing during an infectious process. It has been stated that internalization and phagocytosis mechanism was alternative and defined the destiny of a causative agent in hepatocyte and macrophage as well as the possibility of granulomas formation and of their reverse development.